The impact of biological interventions on health‐related quality of life in adults with Crohn's disease - Stanic Benic, Mirjana (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To systematically assess the beneficial and harmful effects of the biologic treatment on HRQoL outcomes in people with Crohn’s disease.